Abiotic drivers of spawning and early life stage assemblage dynamics of Great Plains fishes - Krellwitz, Elle McKenna (My University, 2025)
The hydrologic regime is a primary driver of environmental conditions in rivers and plays a key role in structuring fish assemblages. Fish have adapted life history strategies in response to natural flow and temperature regimes that provide spawning cues and influence recruitment success. However, the extent to which abiotic factors shape early life stage assemblage structure, particularly hatching and recruitment, remains understudied in Great Plains rivers where fish are adapted to stochastic hydrologic regimes. We used multivariate models to assess the influence of discharge, temperature, and season on early life stage fish assemblage structure in the Kansas and Marais des Cygnes rivers. We also developed length-at-age models to estimate hatch dates and evaluate how hatch timing aligns with environmental conditions. Early life stage assemblages exhibited chronological patterns in abundance, with large-bodied species such as common carp Cyprinus carpio and longnose gar Lepisosteus osseus peaking in late spring, while small-bodied species such as red shiner Cyprinella lutrensis and western mosquitofish Gambusia affinis remained abundant throughout the summer. Hatch frequency exhibited predictable patterns based on life history strategy, with opportunistic species hatching continuously over extended periods, while periodic species hatched intermittently, often coinciding with flow pulses. These findings highlight the need for a nuanced approach to environmental flow management that accounts for species-specific responses to variable hydrologic conditions. Future research in the Kansas and Marais des Cygnes rivers should focus on identifying hatch timing and recruitment patterns for species of conservation concern to capture effects of hydrological variation and better inform conservation efforts.
Keywords: Great Plains; Life history; Larval fish